Analiz psichofiziologiceskogo sostojanija basketbolistov na trenirovocnom etape - Li, Y. F.; Baishev, A. A.; Korkin, E. V.; Cherkashin, I. A.; Smetanin, N. Y. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article presents data on the analysis of the psychophysiological state according to indicators of the individual typological properties of higher nervous activity and the sensorimotor functions of basketball players at the training stage. It has been revealed that for the basketball players, the diagnosis of the neurodynamic properties of higher nervous activity and sensorimotor functions, which significantly affect the effectiveness of competitive activity of athletes, is of great importance, these include: latent time indicators of simple and complex sensorimotor reactions, the number of decision errors, as well as indicators characterizing strength, mobility of HNA. The average values of the indicators of the psychophysiological state of basketball players were determined: LP SSMR - 365.36±51.19 ms, the number errors SSMR - 2.00±1.33, LP PS1-3 - 501.18±34.76 ms, the number errors PS1-3 - 1.55±1.29, LP RS 2-3 - 527.64±37.14 ms, the number of errors RS2-3 - 2.64±2.01, LP LFMNP - 430.91±29.08 ms, the number of errors LFMNP - 23.09±4.13, the total time for performing the LFMNP test - 109.55±13.73 s, the time for reaching the minimum exposure - 69.82-12.77 s, and the LP SNP - 394.64±15.58 ms, the number of exposures - 293±15.36, the minimum exposure time of the signal - 325.45±23.8 ms, the time to reach the minimum exposure - 135.9±31.61 s. It was determined that the overwhelming majority of athletes examined had a strong and mobile type of higher nervous activity, which is due to the specifics of the sports activities of game sports representatives, in particular, basketball.